Inhibitory effects of laminaran and alginate on production of putrefactive compounds from soy protein by intestinal microbiota in vitro and in rats. (5th June 2016) - Nakata, Toru; Kyoui, Daisuke; Takahashi, Hajime; Kimura, Bon; Kuda, Takashi
Highlights: In Japan, soybean based food items are often consumed with brown algae. Laminaran and alginate are fermentable polysaccharides in brown algae. They inhibited putrefactive compound production by human faecal microbiota. They also inhibited caecal putrefactive compounds in rats fed high soy protein diet. Microbiota changes in the rats were obtained with 16S rDNA-DGGE and pyrosequencing. Abstract: Soybean is one of the major components of the Japanese diet. In traditional Japanese cuisine, soybean-based food items are often consumed with brown algae. In this study, we examined the effect of water-soluble and fermentable polysaccharides, laminaran and sodium alginate, from brown algae, on putrefactive compound production, by human faecal microbiota in broth containing 3% (w/v) soy protein. We also investigated the effect of 2% laminaran or alginate diet on caecal putrefactive compounds in rats maintained on diets containing 20% (w/w) soy protein. The caecal microbiota was also analysed using denaturing gradient gel electrophoresis and pyrosequencing with primers targeting the bacterial 16S rRNA gene. The polysaccharides, particularly laminaran, inhibited ammonia, phenol, and indole production by human faecal microbiota. Both the algal polysaccharides lowered the caecal indole content. Laminaran was found to increase the number of Coprobacter, whereas Helicobacter was found to decrease in the presence of both laminaran and sodium alginate.